Relationship between organizational factors and organizational learning / Syahrul Nadwani Abdul Rahman, Wan Maziah Wan Ab Razak and Sakinat Mat Zin - Abdul Rahman, Syahrul Nadwani; Wan Ab Razak, Wan Maziah; Mat Zin, Sakinat (Research Management Institute (RMI), 2012)
Workplace learning is vital. Even routine practices such as strategic environmental assessments can provide a springboard for learning and the emergence of hybrid practitioners can mobilize new networks (Crawford, 2010). Individual learning and the organizational ability to tap into that knowledge are thought to be important to an organization’s success. Englehardt and Simmons (2002) believed that the importance of learning to organizational performance has, among other things, been cited as a key element of flexible capabilities. This study is conducted to examine the relationship between organizational factors namely staff interaction, technology facilities and rewards as independent variables, with the dependent variable which is organizational learning. In order to measure the level of organizational learning, four dimensions that will be utilized are (a) detection and correction of error; (b) modification of routine and behaviour; (c) improvement of capability; and (d) development of new knowledge. This study is carrying out on UiTM Terengganu Staffs. Approximately 254 staffs in the campus will become the subject of the study. The descriptive analysis of mean range is used to assess the level of all dimensions for organizational factors and organizational learning. Meanwhile Correlation and Regression analysis is used to examine the relationship between organizational factors and organizational learning. Hopefully, after implementing this research it will help the organization to give more attention on the factor that encourage the learning process in the organization as well as to better developed and enhance the other factor that might be contributed to the organizational learning, so that, the organization will always obtains knowledgeable workers and competitive working environment. It also could be linked to the investment that organization has made in order to provide the workers with training and development program in respect of training effectiveness.